Complete chloroplast genome of a high-quality forage in north China, Medicago ruthenica (Fabaceae：Trifolieae). Issue 1 (2nd January 2021) - Xie, Jiuxiang; Mao, Junping; Li, Zongren; Liang, Chengbo; Ou, Weiyou; Tang, Junwei; Liu, Hua; Wang, Haichun; Ji, Zhongke; , Kazhuocairang; Shen, Yingfang
Abstract: Medicago ruthenica is a well-known high-quality forage due to its good palatability and strong tolerance to drought, cold and saline-alkali stress. Here, the complete chloroplast genome sequence of M. ruthenica was reported. The chloroplast genome is 126, 939 bp in length. This chloroplast genome has no inverted repeat (IR) regions, which is very common in the family Fabaceae. The M. ruthenica chloroplast genome encodes 107 genes, including 73 protein-coding genes, 30 tRNA genes, and 4 rRNA genes. Phylogenetic analysis result strongly suggested that M. ruthenica is a distinct lineage in Medicago, being sister to highly supported clade composed of three species ( M. hybrida, M. papillosa and M. sativa ).